USING DIGITAL TECHNOLOGY TO TRAIN FUTURE TRANSLATORS (Modern education and development, 2025)
The translation profession has been profoundly influenced by digital advancements, making technological proficiency an essential skill alongside linguistic expertise. In today’s professional landscape, translators must demonstrate competence in computer-assisted translation (CAT) tools, machine translation (MT), and localization software to meet industry demands. As globalization necessitates high-quality multilingual communication, training programs must evolve to equip future translators with both technical and linguistic skills (Golovatska & Tereshchuk, 2024). This article explores the role of digital tools in modern translator education, analyzing their advantages, challenges, and the shifting requirements of the linguistic services market.